Rage, revenge, reward, and recreation: Validating short-form measures of adolescents' aggression across offline and online contexts - Graf, Daniel; Yanagida, Takuya (SAGE PUBLICATIONS LTD, 2026)
The quadripartite violence typology categorizes aggression into rage, revenge, reward, and recreational aggression. Furthermore, the general aggression model highlights the interaction between personal and contextual factors in shaping aggressive behavior. Whereas the four types of aggression are considered as personal factors, a contextual distinction can be made between offline and online contexts. To date, only the Cyber-Aggression Typology Questionnaire (CATQ) and its offline counterpart, the Face-to-Face Aggression Typology Questionnaire (FATQ), operationalize each aggression type specifically for offline and online settings. However, this questionnaire set presents limitations in its applicability due to its item count and exclusive validation in university students. In this two-study article, we developed and validated short versions (CATQ-S/FATQ-S) utilizing Graf et al.'s original dataset (N = 587 university students, Study 1) and revalidated them in a new sample of secondary school students (N = 1,064, Study 2). In Study 1, structural validity of the CATQ-S/FATQ-S could be confirmed. All scales of the CATQ-S showed acceptable to good reliabilities. Whereas the revenge and recreational aggression scales of the FATQ-S showed acceptable to good reliabilities, the reliabilities of its rage and reward scales were slightly below the threshold of .70. All short scales showed substantial correlations with their corresponding full scales. Similar correlational patterns for the short and full scales with external criteria could be found. In Study 2, structural validity of the CATQ-S/FATQ-S could be confirmed. All scales of the CATQ-S/FATQ-S showed acceptable to good reliabilities and criterion validity was largely observed. This research supports the four-factor model of aggression in both offline and online contexts and provides a practical instrument designed for the efficient measurement of four-factor aggression in secondary schools.